Liberalization and the social sector in Jamaica. - Girvan, Norman P. (1992)
Discusses the impacts of liberalization at (1) the macro level and at (2) the sector level, where (1) there is a reduced standard living of all those in the social service, and (2) there are cuts in the provision of social services to the public.